Evaluating the Role of Augmented Reality in Enhancing Engagement and Learning in TVET Education: A Scoping Review - Yee Peng, Chua; Mohd Kamaruzaman, Fathiyah; Omar, Marlissa (Journal of Applied Science, Engineering, Technology, and Education, 2025)
immersive learning environments that enhance practical skills, engagement, and conceptual understanding. Despite its promise, AR adoption in TVET is still limited, often hindered by high costs, lack of infrastructure, and insufficient training for instructors. This scoping review explores how AR is being used in TVET settings, based on 17 peer-reviewed articles published between 2020 and 2024 in Scopus and Web of Science databases. Following Arksey and O’Malley’s framework and PRISMA guidelines, the review identified three main themes: the benefits of AR in simulation-based learning and student engagement; key barriers including cost and technical challenges; and the importance of digital literacy and institutional support in successful implementation. While AR shows strong potential to bridge the gap between theory and hands-on practice, more needs to be done to ensure its sustainable use. The findings offer practical insights for educators, researchers, and policymakers, stressing the need for better infrastructure, continuous professional development, and more long-term studies to fully realize AR’s role in preparing students for modern industry demands.